Organizational strategy for the development of nurses' competences: possibilities of Continuing Education in Health - Amanda de Lemos Mello; Lana Jocasta de Souza Brito; Marlene Gomes Terra; Silvia Henriques Camelo (Universidade Federal do Rio de Janeiro, 2018)
ABSTRACT Objective: To reflect on Continuing Education in Health as an organizational strategy for the development of nurses' competences. Methods: A theoretical-reflective study was performed, combining concepts from Continuing Education in Health, organizational strategy and professional competence, understood as key elements for the work of nurses in health services. Results: To understand how to live together, individuals need to have knowledge about others, their history and traditions. When "learning how to do", they acquire broader competence to deal with unexpected situations and to facilitate team work. With regard to "learning how to be", they are encouraged to acquire autonomy and discernment on behalf of the group. If the focus is on development rather than control, there is shared interest and an integrated and strategic model for nurses' competences to be improved. Conclusion: The development of competences in nurses is the basis for the Learning Paths as a possible operationalization of Continuing Education in Health.